Storytelling, History, and the Postmodern South - Phillips, Jason, 1973- (Book collections on Project MUSE., 2013)
On November 5, 1968, Ralph Ellison stood up at the Southern Historical Association meeting in New Orleans and called the members gathered there "respectable liars," thus exposing the link between "official" history and the dominant consciousness of the time. The author, a historian, refers to such scholarship as "master narratives" - stories masquerading as truth that promote the interests of white patriarchy past and present. In this collection, the author and ten other historians and literary scholars explore an enduring dynamic between history, literature, and power in the American South.